FACTORS AFFECTING ECONOMIC PERFORMANCE THROUGH PARTICIPATION OF ZAKAT RECIPIENT IN DEVELOPING BUSINESS - Estiningsih Estiningsih; Sundari Sundari (Universitas Gunadarma, 2019)
Community empowerment is a form of development which directly involves the community. In community empowerment program, the position of the community is as program consumer but as program producer instead. Community empowerment aims to achieve community independence and welfare. Zakat is a subsystem which can support community empowerment program. It’s consistent with the objective of zakat, which is material and spiritual wellbeing. To encourage the success of the program, there should be support from various parties, including companion and social capital supports.The purpose of the present study was determining the direct effects of companion and social capital on participant of zakat recipient and its impact of economic performance of zakat-receiving micro businessman. The present study used primary data by involving 72 zakat-receiving micro businesspeople (mustahik businesspeople) in Wonosari Sub-district, Gunung Kidul Regency, Special Region of Yogyakarta. The research instrument was questionnaire with likert-5 scale which has high reliability and validity based on Cronbah Alpha and Kaiser-Meyer-Olkin values. The empirical model was analyzed using Structural Equation Modeling (SEM).The result of hypothesis test shows that companion and social capital affected the participation of zakat recipient, and the participation of zakat recipient affected the economic performance of zakat-receiving micro businessman.